PENGGUNAAN MODEL PEMBELAJARAN JIGSAW DAN SNOWBALLING DITINJAU DARI MOTIVASI BELAJAR DAN KEMAMPUAN MEMORI SISWA - Nurhayati, Arin (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
The research purpose was to know the effect of Jigsaw and Snowballing learning models, learning motivation and memory capacity of students toward student achievement.The samples of the research consisted of 2 classes from State Junior High School 1 Baki. The first experimental class treated with Jigsaw learning model and second experimental class treated with the Snowballing leraning model. The data was collected using test and questionere. The hypotheses were tested using Anova and continued by comparison test. From the data analysis can be concluded that 1) The achievement of student who learnt using Jigsaw was higher than them who learnt using Snowballing ; 2) The achievement of students who have higher learning motivation was higher than those who have lower learning motivation; 3) The achievement of students who have higher memory capacity was higher; 4) there was no interaction between the learning model with the learning motivation; 5) there wasÂ interaction between learning model with the memory capacity on student achievement; 6) there was no interaction between learning motivation with the memory capacity on science learning achievement; 7) There was no interaction between cooperative learning with learning motivation and the memory capacity on science learning achievement.Â Kata kunci: Model Pembelajaran Jigsaw dan Snowballing, Motivasi Belajar, Kemampuan Memori, Prestasi belajar.